2021
DOI: 10.3329/bjms.v20i5.55616
|View full text |Cite
|
Sign up to set email alerts
|

​Key findings regarding COVID 19 in Bangladesh and wider and their implications

Abstract: not available Bangladesh Journal of Medical Science Vol.20(5) 2021 p.199-205

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…This includes issues with hydroxychloroquine, lopinavir/ritonavir, remdesivir and ivermectin, with robust studies suggesting limited clinical benefit, although systematic reviews have suggested remdesivir can accelerate clinical improvement [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. This is a concern as misinformation can increase morbidity, mortality and costs [ 50 , 51 , 52 , 53 ]. Concerns with misinformation have resulted in groups, including the World Health Organization (WHO) and the British Medical Journal (BMJ), providing evidence-based guidance [ 54 , 55 , 56 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…This includes issues with hydroxychloroquine, lopinavir/ritonavir, remdesivir and ivermectin, with robust studies suggesting limited clinical benefit, although systematic reviews have suggested remdesivir can accelerate clinical improvement [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. This is a concern as misinformation can increase morbidity, mortality and costs [ 50 , 51 , 52 , 53 ]. Concerns with misinformation have resulted in groups, including the World Health Organization (WHO) and the British Medical Journal (BMJ), providing evidence-based guidance [ 54 , 55 , 56 , 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current COVID-19 pandemic, and subsequent preventative measures to limit the spread of the virus, including social distancing measures, closure of borders, and cancelling of clinics, has resulted in considerable economic and healthcare consequences across countries [1][2][3] . This includes issues with the routine immunisation of children, increasing future morbidity and mortality, although programmes are ongoing in Bangladesh to improve the situation 2,4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…High AMR rates are a major issue in Bangladesh although there are ongoing Government and other activities to try and reduce these 19,[23][24][25][26][27] . Alongside this, we are aware that there was appreciable misinformation during the pandemic surrounding potential treatments for patients with COVID-19 1 . This included misinformation surrounding hydroxychloroquine, which resulted in increased costs, morbidity and mortality 1,28,29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are also aware that the transition to online learning has not been easy for a number of faculty members and students 58 . Identified issues included appreciable variations in the necessary skills among both faculty staff members and students to conduct teaching and interactions on-line at the start of the pandemic, exacerbated by poor computer skills among some faculty members and students [59][60][61][62][63] . Alongside this, the necessary ICT equipment including laptops alongside available, reliable and affordable internet facilities, as well as quiet rooms, to fully undertake e-learning 50,57,62,[64][65][66] .…”
mentioning
confidence: 99%